SPATIO-TEMPORAL FEATURE OF THE HORTICULTURE PRODUCTION EFFICIENCY IN KHARKIV REGION - Добровольська, Наталія (Human Geography Journal, 2016)
The article deals with features analysis of the crop production efficiency in agricultural enterprises of Kharkiv region. The horticulture is proved to be one of the most stable and profitable production sectors in Ukraine. Importance of profitability determination and sale crop products at the regional level for the expedience identification of the future agriculture development is focused in the article. The dynamic of the sale average prices and sale indexes of the main crops was analyzed, as well as districts-leaders and districts-outsiders of Kharkiv region by the efficiency level and oil, cereals, legumes, sugar beat sale were  determined.